Molecular mobility in the gap regions of type 1 collagen fibrils. Issue 2 (February 1986) - Fraser, R. D. B.; Trus, B. L.
Abstract : Recent studies of the structure of Type I collagen fibrils (Piez and Trus, Biosci. Rep. 1 :801–810, 1981; Fraser, MacRae, Miller and Suzuki, J. Mol. Biol. 167 :497–521, 1983) suggest that the segments of the collagen molecule which comprise the gap region are more mobile than those which comprise the overlap region. We have analyzed the distribution of amino acid residues and triplet types between the two regions, and find significantly non-uniform distributions for Ala, Gln, His, Hyp, Leu, Phe, and Tyr, and for triplets containing two imino acid residues. Taken together with the lower packing density in the gap region these observations provide a basis for understanding the greater mobility of the molecular segments in the gap region. In addition, we have examined the linear distribution of residue types in the two regions and also the hydropathy profile (Kyte and Doolittle, J. Mol. Biol. 157 : 105–113, 1982). These reveal a segment of the gap region comprising helical residues 165–173, 399–407, 633–641 and 867–975 which has the highest hydropathy index, is devoid of charged residues, and contains very high proportions of Ala, Hyp and Phe.